Optimization of the Oertli CataRhex 3® phacoemulsification machine - Stutz LA (Dove Medical Press, 2019)
Lance A Stutz,1 Joshua B Heczko,2 Brian A Bird,3 Rhett S Thomson,2,4 Ashlie A Bernhisel,2 William R Barlow,2 Brian Zaugg,2 Randall J Olson,2 Jeff H Pettey2 1University of Texas Southwestern Medical School, University of Texas Southwestern Medical Center, Dallas, TX 75390, USA; 2Department of Ophthalmology and Visual Sciences, John A Moran Eye Center, University of Utah, Salt Lake City, UT 84132, USA; 3University of Nevada Reno, School of Medicine, Reno, NV 89557, USA; 4University of Utah, School of Medicine, Salt Lake City, UT 84132, USA Purpose: The aim of this study was to determine optimal bottle height, vacuum, aspiration rate, and power settings of the Oertli CataRhex 3® phacoemulsification machine. Methods: Porcine lens nuclei were hardened with formalin and cut into 2.0 mm cubes. Lens cubes were emulsified using the easyTip® 2.2 mm at 30°. Fragment removal time (efficiency) and fragment bounces off the tip (chatter) were measured. Settings tested included bottle height of 60, 80, 100 and 120 cm; aspiration rate of 40, 45, and 50 mL/min; vacuum of 400, 500, and 600 mmHg; and power of 50, 60, 70, 80, 90, and 100%. Results: Efficiency and chatter increased in a linear fashion with increasing vacuum to 600 mmHg (P=0.017, P=0.046, respectively). The most efficient aspiration rate was 50 mL/min, although this finding lacked statistical significance (P=0.66). Increasing power increased efficiency up to 80% without increasing chatter (P=0.042, P=0.71, respectively). Compared to all other power settings, chatter was increased at 100% (P=0.014). Conclusion: The most efficient machine settings were vacuum at 600 mmHg, aspiration rate at 50 mL/min, and power at 80%. Keywords: cataract, blindness, underserved countries, vacuum, aspiration rate, power